2021
DOI: 10.3390/ph14100969
|View full text |Cite
|
Sign up to set email alerts
|

Posidonia oceanica (L.) Delile Extract Reduces Lipid Accumulation through Autophagy Activation in HepG2 Cells

Abstract: Posidonia oceanica (L.) Delile is a marine plant traditionally used as an herbal medicine for various health disorders. P. oceanica leaf extract (POE) has been shown to be a phytocomplex with cell-safe bioactivities, including the ability to trigger autophagy. Autophagy is a key pathway to counteract non-alcoholic fatty liver disease (NAFLD) by controlling the breakdown of lipid droplets in the liver. The aim of this study was to explore the ability of POE to trigger autophagy and reduce lipid accumulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Accordingly, these results support the efficacy and reproducibility of hydroalcoholic extractions from P. oceanica leaves [ 26 , 27 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Accordingly, these results support the efficacy and reproducibility of hydroalcoholic extractions from P. oceanica leaves [ 26 , 27 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 73%
“…The hydroalcoholic extraction protocol, previously described [ 26 , 34 ], was applied to 4 g of dried and minced leaves of P. oceanica . The total yield of P. oceanica dry extract was 45 mg. POE was constituted by resuspending 1.8 mg of dry extract in 0.5 mL of EtOH 70% ( v / v ), yielding a hydrophilic analyte concentration of 3.6 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Posidonia oceanica is a marine plant used in traditional medicine for the treatment of several health conditions, such as diabetes and inflammation. The aim of the study carried out by Vasarri et al [ 4 ] was to analyze the ability of P. oceanica hydroalcoholic extract to trigger autophagy and reduce intracellular lipid accumulation, in an in vitro model of hepatic steatosis using the human hepatoma cell line HepG2. The authors found that the extract protected against lipid accumulation in HepG2 cells by promoting autophagy through inhibition of the mTOR pathway, offering new insights for possible complementary treatments of non-alcoholic fatty liver disease.…”
mentioning
confidence: 99%